FÖTAL VE POSTNATAL DÖNEMDE RAT OVARYUMLARININ HİSTOGENEZİSİ ÜZERİNDE IŞIK MİKROSKOBİK ÇALIŞMALAR - YECAN, NURHAYAT (Fırat Üniveristesi, 1994)
Bu araştırmada 20 adet ergin dişi, 5 adet ergin erkek, ortalama 40 adet 14- 21 günlük dişi fötüs, 20 adet yeni doğmuştan 60 günlüğe kadar olan dişi ratlar kullanıldı. Hayvanlardan elde edilen ovaryumlardan hazırlanan histolojik preparatlar ışık mikroskobunda incelendi. Fötal gelişim başlangıcında ovaryumların yüzeyi kübik epitel hücreleriyle kaplıydı. Prenatal 18. günden itibaren yüzey epiteli kübikten yassıya değişiyordu. Prenatal 16. günde yüzey epitelinin altında ovogonyumlar kordonlar oluşturmuştu, 18. günde kordonların boyları kısalmış ve ovogonyumlar, granüloza hücreleriyle sarılmış gruplar oluşturmuştu. Prenatal 20. günde medulla- korteks ayrımı yapılabiliyordu ve primordiyal folliküller şekillenmeye başlamıştı. Prenatal yaşam boyunca ovogonyum ve granüloza hücrelerinde mitoz devam ediyordu. Ayrıca dejenere ovogonyumlara rastlanıyordu. Postnatal 3. günde primordiyal folliküller çok artmıştı, primer folliküllere de ilk defa bu günde rastlandı, ilk sekunder folliküller postnatal 4. günde meydana gelmeye başladı. Bu günde sekunder folliküller içindeki ovositlerde zona pellusida ilk defa gözlendi. Primer folliküllerde zona pellusida ilk olarak 7. günde görüldü. 12 günlük yavru ovaryumunda her aşamadaki folliküllere rastlanıyordu. İlk defa bu günde antrum şekillenmiş folliküller gözlendi. Antrum şekillenmiş folliküllerde ve gelişmiş sekunder folliküllerde teka interna ve ekstema belirgindi, ayrıca atretik folliküller gözleniyordu. 26 günlük genç hayvanların ovaryumunda intersitisyumun arttığı dikkati çekiyordu. Ergin hayvanların ovaryumlarında kübikten yassıya değişen yüzey24 epiteli, epitelin altında tun ika albugineya ve kortekste değişik aşamalardaki folliküller ile korpus luteum gözleniyordu. Prenatal ve postnatal dönemlerde çapları ölçülen ovosit ve folliküllerin gelişmeye paralel olarak büyüdüğü, zona pellusida kalınlığının ise postnatal 18. güne kadar arttığı bu günden sonra sabit kaldığı gözlendi.

In this study 20 mature female and 5 mature male rats, 40 female rat fetuses 14- 21 days old, and 20 immature female rats aging up to 2 months old were used. The histologic sections of ovaries from the animals were examined under the light microscope. In the beginning of the fetal development, surfaces of ovarians vere covered with cuboidal ephitelial cells. Surface ephitelium were chanced from cuboidal to flattened surface ephitelium from the day 18 prenatal onwords. Oogonia present under the surface ephitelium started to form cords at the 16tn day of prenatal period. At the 18tn day of prenatal period, the length of the cords were shortened and oogonia were grouped together and these groups were covered with granulosa cells. At the day 20 in the same period, it was possible to differetiate medulla and cortex and primordial follicles appeared to form. Throughout the prenatal life, the mitotic division continued in the oogonium and granulosa cells and occasional degenerative oogonia were present. There was significant increase in the number of primordial follicles at the day 3 postnatal period. For the first time, primer follicles were obserwed during the same period. At day 4 postnatal period, secondary follicles started to be detected. Furthermore, zona pellucida at the oocytes in the secondary follicles were first observed during this time. In this study it was noticed however, primary follicles also had zona pellucida at the day 7 postnatal period. At 12th day postnatal ovarium, follicles from all developmental stages were present. For the first time follicles with antrum appeared at this day. Theca interna and externa were26 obrious in secondary follicles and in follicles with antrum. Furthermore, during this time, it was possible to observe atretic follicles. In the young animals 26 days old, there was increase in the interstitium present in ovarium. In the ovariums of mature animals, surface eptihelium returned from cubic to flattened form. Tunica albuginea under the epithelium was noticeble in ovariums of mature animals. Also follicles in the different developmental stages and corpus luteum were present in the ovarial cortex. During prenatal and postnatal periods, diameters of oocytes and follicles were measured. These results indicated that the diameters of oocytes and follicles increased to according to developed. The thickness of zona pellucida increased until the 18tn day of postnatal period. Afterwords there was no change in the zona pellucida.
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Veteriner Hekimliği; Veterinary Medicine